Antibacterial Activity Test of Tembelekan Leaf Ethanol Extract (Lantana camara L) Against Bacteria Causing Gastrointestinal Tract Infections - Hajar, Siti; Fitriana, Fitriana; Asmaliani, Ira (PHARMACY UMI JOURNAL SYSTEM, 2023)
Tembelekan leaves have been shown to be efficacious as antioxidants, anticancer, antibiotics, antibacterial, which are known to contain alkaloids, saponins, flavonoids, and tannins. The purpose of this study was to determine the antibacterial activity of the ethanol extract of tembelekan leaves (Lantana camara L) against bacteria that cause digestive tract infections. The method used in this research is agar diffusion. Antibacterial screening test with concentrations of 0.1%, 0.5% and 1% against test bacteria E.Coli, S.Dysenteriae, V.Cholerae, S.Typhi. After that, MIC, KBM, and antibacterial activity testing were carried out. The results of the screening test gave activity at a concentration of 1% against the four test bacteria. The MIC test value obtained a concentration of 0.5% on E. Coli bacteria and V. cholerae bacteria, a concentration of 0.25% on S. Dysentriae bacteria and S. typhi bacteria. KBM value of 1% concentration on E. coli and V. Cholerae bacteria, 0.5% concentration on S. Dysentriae and S.typhi bacteria. The results of the antibacterial activity test of the ethanol extract of tembelekan leaves against the test bacteria obtained the largest diameter of the inhibition zone at a concentration of 20%. Based on the research, the ethanol extract of tembelekan leaves has antibacterial activity.